Pendampingan Sertifikasi Kompetensi sebagai Upaya Meningkatkan Employability Skills bagi Siswa SMA Muhammadiyah 8 Ciputat - Pertiwi, Indah; Lubis, Metha (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve the employability skills of SMA Muhammadiyah 8 Ciputat students through competency certification assistance. The implementation method includes competency certification socialization, competency test preparation assistance, assessment simulations, and evaluation of the activity implementation. The target of the activity is SMA Muhammadiyah 8 Ciputat students in their final year. The results of the activity indicate an increase in students' understanding of the importance of competency certification, an increase in technical and non-technical competencies, and an increase in students' motivation and confidence in facing the world of work. In addition, students demonstrated better preparedness in participating in the competency certification process. This activity also strengthens the synergy between schools and universities in efforts to develop student competencies. Thus, competency certification assistance can be an effective strategy in improving the employability skills of high school students and can be used as a model for developing similar programs in other high schools. Keywords: competency certification, employability skills, mentoring, high school students, community service